Sensing in the Mouth: A Model for Filiform Papillae as Strain Amplifiers - Lauga, Eric; Pipe, Christopher J.; Le Révérend, Benjamin (Frontiers in Physics, 2016)
Texture perception of foods is a common yet remarkably unstudied biophysical problem. Motivated by recent experiments reporting the presence of corpuscular endings in tongue filiform papillae, we develop in this work a mechanical model of the human tongue covered with filiform papillae in the form of elastic beams. Considering the typical flows that occur in the mouth during oral evaluation of Newtonian liquids, we suggest that filiform papillae may act either as direct strain sensors and/or as indirect strain amplifiers for the underlying mucosal tissue. Application of this model may also be valid for other biological appendages, such as primary cilliae and superficial neuromasts.